Estimating a Supply Block for Poland - Kierzenkowski, Rafal (OECD Publishing, 2008)
The supply-side framework and related measures of output and unemployment gaps play a leading role in the OECD analysis of short-term conjunctural conditions and long-term determinants of growth. To allow such diagnoses for Poland, this paper develops a comprehensive supply block in accordance with the OECD approach. The structural unemployment rate is derived from a Phillips-curve equation and, along with working age population, is combined with filter-based estimates of trend labour productivity, participation rates and hours worked per employee to generate measures of potential output. The performance of the model in capturing price pressures underlying the growth trajectory of the Polish economy is assessed, and measures of cyclically-adjusted general government net lending are provided. Based on the OECD autumn 2007 projections for 2008 and 2009, out-of-sample simulations derived from the Phillips-curve model suggest that CPI inflation is likely to continue to trend upward, exceeding the central bank?s inflation target by a wide margin
Keywords: Economics; Poland